2015
DOI: 10.1016/j.jjie.2015.05.006
|View full text |Cite
|
Sign up to set email alerts
|

Abenomics: Why was it so successful in changing market expectations?

Abstract: a b s t r a c tFukuda, Shin-ichi-Abenomics: Why was it so successful in changing market expectations? 'Abenomics' refers to a new unconventional economic policy regime in Japan since late 2012. It consists of three arrows: unconventional monetary policy (the first arrow), expansionary fiscal policy (the second arrow), and economic growth strategies to encourage private investment (the third arrow). After the new regime started, both the stock and the foreign exchange markets reacted very favorably. The purpose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(28 citation statements)
references
References 24 publications
0
28
0
Order By: Relevance
“…Prime Minister Shinzo Abe undertook a set of economic policies known as 'Abenomics', which include unprecedented and unconventional expansionary monetary policy and two fiscal policy packages (expansionary fiscal stimulus and structural reform) to stimulate economic growth (Fukuda, 2014). Implementation of Abenomics resulted in the devaluation of the Yen and corporate reform over the years (Economist, 2015.…”
Section: Introductionmentioning
confidence: 99%
“…Prime Minister Shinzo Abe undertook a set of economic policies known as 'Abenomics', which include unprecedented and unconventional expansionary monetary policy and two fiscal policy packages (expansionary fiscal stimulus and structural reform) to stimulate economic growth (Fukuda, 2014). Implementation of Abenomics resulted in the devaluation of the Yen and corporate reform over the years (Economist, 2015.…”
Section: Introductionmentioning
confidence: 99%
“…The depreciation of the yen/dollar nominal exchange rate in the post‐Plaza accord exhibits a common stochastic trend of the yen/dollar rate, which is dictated by the monetary base differential between the two countries. Fukuda () advances the hypothesis that the news shocks about Abenomics was successful in changing market expectations in stock prices and the yen/dollar rate. Favorable responses to news on Abenomics by foreign investors led to improving market sentiments despite the fact that the news was revealed during the day in Japan.…”
Section: Impulse Responses To Qe Shocksmentioning
confidence: 99%
“…They find some cases in which the policy announcements have significant effects on the exchange rate. Also, in relation to the current round of monetary easing in Japan, Fukuda (2015) shows that investors, most notably foreign investors, reacted to recent series of expansionary policy announcements. Ueda (2013) also agrees with the view that the strong yen depreciation was a reaction to the aggressive monetary policy stance.…”
Section: Unconventional Monetary Policy and The Exchange Rate Channelmentioning
confidence: 99%
“…A massive depreciation of the Japanese yen was observed since late 2012, which was most likely a reaction to the announcement of a massive monetary expansion by the newly formed government led by Shinzo Abe (Fukuda (2015) and Kano and Morita (2015)). However, recent studies have repeatedly found a tendency of a declining exchange rate pass-through to domestic prices, both in Japan and in many other countries.…”
Section: Introductionmentioning
confidence: 99%